Metabolic Profiling Reveals Diagnostic Biomarkers for Distinguishing Myocarditis From Acute Myocardial Infarction - Yuting Chen; Xiu Liu; Chengying Hong; Shunyao Xu; Linling He; Zhenmi Liu; Huaisheng Chen; Yaowang Lin (Cardiovascular Therapeutics)
Conclusions: In conclusion, patients experiencing AMI and MC undergo significant metabolic reprogramming. Metabolites exhibiting abnormal expression in peripheral blood hold diagnostic value for distinguishing between AMI and MC in clinical settings. 11-cis-retinol proved to be the pivotal biomarker for AMI, potentially aiding in the development of a robust predictive model for distinguishing between MC and AMI in clinical settings.